2022
DOI: 10.3171/2021.10.jns211794
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the updated Brain Injury Guidelines for complicated mild traumatic brain injuries: a retrospective cohort study

Abstract: OBJECTIVE Approximately 10% of patients with mild traumatic brain injury (mTBI) have intracranial bleeding (complicated mTBI) and 3.5% eventually require neurosurgical intervention, which is mostly available at centers with a higher level of trauma care designation and often requires interhospital transfer. In 2018, the Brain Injury Guidelines (BIG) were updated in the United States to guide emergency department care and patient disposition for complicated mild to moderate TBI. The aim of this study was to val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This study demonstrates that the mBIG algorithm 5 provides a safe framework to assess patient risk for progression of TBI in this patient population, and therefore, resources can, and should, be assigned accordingly. Several validation studies 6–9 support this. In their prospective analysis using a slight algorithmic variation of the original BIG, 3 Ross et al 7 found that no BIG 1 or BIG 2 patients demonstrated a clinical decline or required any further NSG intervention.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This study demonstrates that the mBIG algorithm 5 provides a safe framework to assess patient risk for progression of TBI in this patient population, and therefore, resources can, and should, be assigned accordingly. Several validation studies 6–9 support this. In their prospective analysis using a slight algorithmic variation of the original BIG, 3 Ross et al 7 found that no BIG 1 or BIG 2 patients demonstrated a clinical decline or required any further NSG intervention.…”
Section: Discussionmentioning
confidence: 75%
“…Of those ICU admissions, most (n = 45, 65.2%) were downgraded in less than 48 hours. For mBIG2 patients, the median hospital LOS was 5 (IQR, [4][5][6][7][8][9] with the majority initially admitted to the ICU (n = 54, 88.5%). Again, most (n = 38, 62.3%) were in the ICU for less than 48 hours (Table 3).…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…To satisfy requirements of this phase of the cBPI pipeline, the team reviewed a decade of studies from different hospital systems totaling over 9000 patients. This research shows that adherence to BIG provides high-quality, safe care for patients 4–7. Waste is reduced by eliminating unnecessary transfers, follow-up imaging, and neurosurgery consults.…”
Section: Define and Certifymentioning
confidence: 77%
“…This research shows that adherence to BIG provides high-quality, safe care for patients. [4][5][6][7] Waste is reduced by eliminating unnecessary transfers, follow-up imaging, and neurosurgery consults. Simultaneously, value is increased by flagging those injuries most likely to need intervention.…”
Section: Define and Certifymentioning
confidence: 99%